Silicon-carbon negative electrode and preparation method thereof, preparation method of silicon-carbon negative electrode material and lithium battery
Through the preparation method of silicon carbon negative electrode material, the mixing of hydroxy silicon material and carbon material and high-temperature treatment of lithium battery negative electrode material is solved, and the high specific capacity and good SEI film stability is achieved, and the electrochemical performance and safety of lithium batteries are improved.
Patent Information
- Application Number
- CN202411786853.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-14
AI Technical Summary
The specific capacity of the existing lithium battery negative electrode material graphite is low, which is difficult to meet the market's demand for energy density. At the same time, lithium dendrites are easily formed during the charging and discharging process, which poses safety risks.
Using the preparation method of silicon-carbon negative electrode material, a silicon-carbon negative electrode material is obtained by mixing hydroxy silicon material with carbon material to form a silicon-carbon gel and undergoing high temperature treatment to obtain a silicon-carbon negative electrode material. This method makes silicon evenly dispersed in the carbon layer to form a carbon-covered silicon composite material.
It improves the electrochemical performance of lithium batteries, and has good SEI film stability and multi-ion transport channels on the basis of meeting high specific capacity, enhancing the cycle stability and safety of the battery.
Smart Images

Figure CN119627073A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium batteries, and in particular to a method for preparing a silicon-carbon negative electrode, a method for preparing a silicon-carbon negative electrode material, a silicon-carbon negative electrode and a lithium battery. Background Art
[0002] The negative electrode material currently used in lithium batteries is usually graphite, however, the theoretical capacity of graphite is only 372mAh / g. Although graphite can provide a fast channel for lithium ions, it is difficult to meet the market demand for lithium battery energy density due to its low specific capacity; in addition, graphite negative electrodes will form lithium dendrites during the charging and discharging process, which poses a safety risk.
[0003] Silicon is abundant in the earth's crust, accounting for 26.7% of the total reserves. Its theoretical specific capacity is as high as 4200mAh / g, and its low redox potential (about 0.4V or less) can avoid safety hazards such as lithium dendrites, thereby improving the safety of batteries. However, silicon-based negative electrode materials are prone to volume expansion during the cycle, resulting in a decrease in the electrochemical performance of the negative electrode during the cycle. Summary of the invention
[0004] The main technical problem solved by the present application is to provide a method for preparing a silicon-carbon negative electrode, a method for preparing a silicon-carbon negative electrode material, a silicon-carbon negative electrode and a lithium battery, which can improve the electrochemical performance of the corresponding lithium battery.
[0005] To solve the above technical problems, a technical solution adopted in the present application is: to provide a method for preparing a silicon-carbon negative electrode material, comprising: obtaining a hydroxyl silicon material; mixing the hydroxyl silicon material with a carbon material to obtain a silicon-carbon gel; and subjecting the silicon-carbon gel to high-temperature treatment to obtain a silicon-carbon negative electrode material.
[0006] Wherein, the carbon material comprises konjac glucomannan.
[0007] Among them, the carbon material is biomass carbon material.
[0008] Among them, the biomass carbon material includes at least one of ice powder and konjac products.
[0009] The method of obtaining the hydroxy silicon material comprises: adding nano silicon particles to a sulfuric acid and hydrogen peroxide mixture to perform a hydroxylation treatment on the nano silicon particles to obtain a hydroxy silicon mixture; and washing the hydroxy silicon mixture to obtain the hydroxy silicon material.
[0010] The method comprises adding nano silicon particles to a sulfuric acid and hydrogen peroxide mixture to perform hydroxylation on the nano silicon particles to obtain a hydroxy silicon mixture, including: adding nano silicon particles to a sulfuric acid and hydrogen peroxide mixture at 80° C. to 85° C. and with a volume ratio of sulfuric acid to hydrogen peroxide of 7-9:1-3, and stirring for 10 min to 30 min to obtain a hydroxy silicon mixture; and washing the hydroxy silicon mixture to obtain a hydroxy silicon material, including: washing the hydroxy silicon mixture with deionized water and ethanol, and then drying the mixture to obtain the hydroxy silicon material.
[0011] The hydroxy silicon material and the carbon material are mixed to obtain the silicon-carbon gel, including: dissolving the hydroxy silicon material in deionized water and heating it to 95°C-98°C to obtain a hydroxy silicon mixed liquid; adding the carbon material to the hydroxy silicon mixed liquid, stirring and cooling to room temperature to obtain the silicon-carbon gel, wherein the mass ratio of silicon to carbon material in the hydroxy silicon material is 1:1-3.
[0012] Among them, the silicon-carbon gel is subjected to high-temperature treatment to obtain the silicon-carbon negative electrode material, including: high-temperature treatment of the silicon-carbon gel to obtain the silicon-carbon material, wherein during the high-temperature treatment process, the temperature is increased by 3°C-5°C per minute to 500°C-800°C and kept warm for 1h-3h; the silicon-carbon material is cooled, cleaned and dried to obtain the silicon-carbon negative electrode material.
[0013] Among them, the preparation method of silicon-carbon negative electrode material also includes: freeze-drying the silicon-carbon gel to obtain freeze-dried silicon-carbon gel; high-temperature treating the silicon-carbon gel to obtain silicon-carbon material, including: high-temperature treating the freeze-dried silicon-carbon gel to obtain silicon-carbon material.
[0014] To solve the above technical problems, another technical solution adopted in the present application is: to provide a method for preparing a silicon-carbon negative electrode, comprising: obtaining a silicon-carbon negative electrode material, wherein the silicon-carbon negative electrode material is prepared by the method for preparing the silicon-carbon negative electrode material as described above; mixing the silicon-carbon negative electrode material with a conductive agent and a binder to prepare a slurry mixture; coating the slurry mixture on the negative electrode current collector, and performing a drying treatment to obtain a silicon-carbon negative electrode.
[0015] In order to solve the above technical problems, another technical solution adopted in the present application is: to provide a silicon-carbon negative electrode, which is prepared by the preparation method of the silicon-carbon negative electrode as described above.
[0016] In order to solve the above technical problems, another technical solution adopted in the present application is: to provide a lithium battery, which includes a positive electrode, a negative electrode, a diaphragm, an electrolyte and a shell, wherein the diaphragm is located between the positive electrode and the negative electrode, and the shell is located around the positive electrode, the negative electrode, the diaphragm and the electrolyte; wherein the negative electrode is a silicon-carbon negative electrode prepared according to the preparation method of the silicon-carbon negative electrode as described above.
[0017] The beneficial effect of the present application is that, different from the prior art, the preparation method of the silicon-carbon negative electrode material of the present application includes: obtaining hydroxy silicon material; mixing hydroxy silicon material with carbon material to obtain silicon-carbon gel; subjecting the silicon-carbon gel to high temperature treatment to obtain silicon-carbon negative electrode material. In this way, the hydroxy silicon material in the silicon-carbon gel can be evenly dispersed, so that in the obtained silicon-carbon negative electrode material, silicon is tightly wrapped in the carbon layer, and the internal micropores are interconnected, so that the obtained silicon-carbon negative electrode has good SEI membrane stability on the basis of satisfying the high specific capacity, and has multiple ion transport channels, thereby improving the electrochemical performance of the corresponding lithium battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. Among them:
[0019] Figure 1 is a schematic flow chart of a method for preparing a silicon-carbon negative electrode material in some embodiments of the present application;
[0020] Figure 2 yes Figure 1 Schematic diagram of the process of step S10;
[0021] Figure 3 yes Figure 1 Schematic diagram of the process of step S20;
[0022] Figure 4 yes Figure 1 Schematic diagram of the process of step S30;
[0023] Figure 5 It is the X-ray diffraction pattern of silicon-carbon anode material;
[0024] Figure 6 This is a comparison of hydroxy silicon material (left) and pure silicon (right) suspended in water for 24 hours;
[0025] Figure 7 It is the X-ray photoelectron spectrum of silicon-carbon anode material;
[0026] Figure 8 This is a scanning electron microscope image of the silicon-carbon anode material;
[0027] Fig. 9 is a schematic flow chart of a method for preparing a silicon-carbon negative electrode in some embodiments of the present application;
[0028] Fig.10 This is the CV curve of the silicon-carbon negative electrode. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0030] This application provides a method for preparing a silicon-carbon negative electrode material. Figure 1 In some embodiments, the method for preparing the silicon-carbon negative electrode material comprises:
[0031] Step S10, obtaining hydroxy silicon material;
[0032] The hydroxy silicon material in this application refers to a structure in which silicon atoms are connected to hydroxyl groups on the surface of the silicon material. By modifying the surface of the silicon material, the electrochemical properties of the final negative electrode, such as the first coulombic efficiency, cycle stability and conductivity, can be improved.
[0033] Among them, the hydroxy silicon material can be obtained by purchase, preparation, etc. When preparing the hydroxy silicon material, the raw materials used can be nano silicon particles, silicon nanowires, etc., and the preparation method can be acid catalysis, silane coupling agent modification, alcohol esterification, surfactant method, polymer grafting modification method, etc., which are not specifically limited here.
[0034] Step S20, mixing the hydroxy silicon material and the carbon material to obtain a silicon-carbon gel;
[0035] The hydroxy silicon material is uniformly dispersed in the obtained silicon-carbon gel. Specifically, the obtained hydroxy silicon material can be first dissolved in a solvent to obtain a hydroxy silicon solution, and then the carbon material is added to the hydroxy silicon solution to obtain the silicon-carbon gel.
[0036] It should be noted that the carbon material used in this embodiment is a carbon material that can form a gel after mixing with a solvent, or the carbon material itself is a gel-like carbon material. The carbon material can be an industrially prepared carbon material, or a biomass carbon material, etc., which is not specifically limited here.
[0037] Step S30, subjecting the silicon-carbon gel to high-temperature treatment to obtain a silicon-carbon negative electrode material.
[0038] Specifically, the silicon-carbon gel can be subjected to high-temperature calcination treatment so that the silicon in the obtained silicon-carbon negative electrode material is tightly wrapped in the carbon layer, thereby forming a carbon-coated silicon composite material.
[0039] In actual operation, the silicon-carbon gel can be cured before being subjected to high-temperature treatment, so that the silicon-carbon gel subjected to high-temperature treatment is in a more stable and uniform state, thereby improving the uniformity of silicon distribution in the obtained silicon-carbon negative electrode material.
[0040] Through the above method, the hydroxy silicon material in the silicon-carbon gel can be evenly dispersed, so that in the obtained silicon-carbon negative electrode material, the silicon is tightly wrapped in the carbon layer, and the internal micropores are interconnected. Therefore, the obtained silicon-carbon negative electrode not only meets the high specific capacity but also has good SEI membrane stability and multiple ion transport channels, thereby improving the electrochemical performance of the corresponding lithium battery.
[0041] In some embodiments, the hydroxy silicon material can be prepared by acid catalysis. Specifically, the hydroxy silicon material can be prepared by using silicon materials such as nano silicon particles, silicon nanowires and a mixture of sulfuric acid and hydrogen peroxide. For details, please refer to Figure 2 In the process of preparing the silicon-carbon negative electrode material, step S10 may include:
[0042] Step S11: adding nano silicon particles to the sulfuric acid and hydrogen peroxide mixture to perform hydroxylation on the nano silicon particles to obtain a hydroxy silicon mixture;
[0043] After the nano silicon particles are added to the sulfuric acid and hydrogen peroxide mixture, they can be immersed for a certain period of time to perform a hydroxylation treatment. The purpose of this step is to form active Si-OH groups on the surface of the nano silicon particles.
[0044] Specifically, nano silicon particles are added to a sulfuric acid and hydrogen peroxide mixture at 80° C.-85° C. and with a volume ratio of sulfuric acid to hydrogen peroxide of 7-9:1-3, and stirred for 10 min-30 min to obtain a hydroxy silicon mixture.
[0045] In this embodiment, the reaction is carried out at a high temperature to increase the hydroxylation rate. Specifically, it can be 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, etc. The volume ratio of sulfuric acid to hydrogen peroxide can be 7:3, 8:2, 9:1, etc. The hydroxylation treatment of the nano-silicon particles is achieved during the stirring process, and the stirring time can be specifically 10min, 15min, 20min, 25min, 30min. It can be selected according to the actual situation and is not limited here.
[0046] Step S12: washing the hydroxy silicon mixture to obtain a hydroxy silicon material.
[0047] After the hydroxylation treatment, the substrate is cleaned with a cleaning agent and dried. Depending on the situation, multiple cleaning methods may be used to remove excess acid and oxidizing agent.
[0048] Specifically, the hydroxy silicon material can be obtained by washing with deionized water and ethanol for three times and then performing vacuum drying.
[0049] In some embodiments, see Figure 3 In the process of preparing the silicon-carbon negative electrode material, step S20 may include the following steps:
[0050] Step S21: dissolving the hydroxy silicon material in deionized water and heating the water to 95° C.-98° C. to obtain a hydroxy silicon mixed solution;
[0051] The heating temperature may be 95° C., 96° C., 97° C., 98° C., etc., which is not limited here. It should be noted that the heating treatment can improve the solubility of the hydroxy silicon material on the one hand, and facilitate the subsequent formation of silicon-carbon gel on the other hand.
[0052] Step S22: adding carbon material to the hydroxy-silicon mixed solution, stirring and cooling to room temperature to obtain silicon-carbon gel, wherein the mass ratio of silicon in the hydroxy-silicon material to the carbon material is 1:1-3.
[0053] The carbon material may be a powdered carbon material that can be converted into a gel state under certain conditions, such as being mixed evenly with the heated deionized water and cooled to obtain silicon-carbon gel. Alternatively, a gel-like carbon material may be directly selected, which is not specifically limited here.
[0054] In some embodiments, the carbon material is a biomass carbon material. It should be noted that biomass carbon materials are low-cost, renewable, easy to process, and have a high specific surface area, which can provide more electrochemical active sites, increase the degree of graphitization, accelerate charge transfer, and promote Li + Adsorption increases the capacity, facilitates ion embedding, and improves electrochemical activity.
[0055] Specifically, in some embodiments, the biomass carbon material comprises konjac glucomannan. Konjac glucomannan, also known as konjac flour C 24 H 42 O 21 , is a water-soluble natural polysaccharide. Konjac glucomannan has unique gel properties. The hydroxyl groups form hydrogen bonds during heating to obtain a hydrogel with a three-dimensional network structure, thereby forming a structurally stable silicon-carbon gel together with the hydroxyl silicon material.
[0056] Furthermore, in some embodiments, the carbon material is selected from at least one of biomass carbon materials containing konjac glucomannan such as ice powder and konjac products. Among them, the ice powder can be edible ice powder, and the konjac product can be at least one of konjac silk, konjac knots, konjac glue, etc., which are not specifically limited here.
[0057] In some embodiments, the selected carbon material is edible ice powder, and in the process of preparing silicon-carbon gel, the mass ratio of silicon to edible ice powder is 1:1-3, specifically 1:1, 1:2, 1:3, etc., which is not limited here.
[0058] In some embodiments, after obtaining the silicon-carbon gel, the silicon-carbon gel may be further processed to obtain a silicon-carbon negative electrode material. For details, please refer to Figure 4 , step S30 may include:
[0059] Step S31: freeze-drying the silicon-carbon gel to obtain freeze-dried silicon-carbon gel;
[0060] It should be noted that freeze-drying the hydrogel can, on the one hand, better preserve the silicon-carbon gel. Silicon-carbon gel contains a large amount of water, which may deteriorate at room temperature due to microbial growth, chemical reactions, etc. Freeze-drying can remove moisture, inhibit microbial growth and chemical reactions, and extend the shelf life of the silicon-carbon gel. Second, it can change the structure of the silicon-carbon gel. During the freeze-drying process, the formation and growth of ice crystals will cause the silicon-carbon gel to form a porous structure. This porous structure can provide more lithium ion storage sites while buffering the stress generated by the charging and discharging of lithium ions. Of course, in some embodiments, the silicon-carbon gel may not be freeze-dried, which is not specifically limited here.
[0061] Step S32: subjecting the freeze-dried silicon-carbon gel to high-temperature treatment to obtain a silicon-carbon material, wherein during the high-temperature treatment, the temperature is increased to 500° C.-800° C. at a rate of 3° C.-5° C. per minute and maintained at that temperature for 1 h-3 h;
[0062] The freeze-dried silicon-carbon gel can be subjected to high-temperature treatment using a tubular furnace, wherein the heating rate and the insulation temperature can be achieved by controlling the tubular furnace.
[0063] Specifically, the heating rate can be 3°C, 4°C, 5°C per minute, etc., the holding temperature can be 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, etc., and the holding time can be 1h, 1.5h, 2h, 2.5h, 3h, etc., and no specific limitation is made here.
[0064] Step S33: Cooling, cleaning and drying the silicon-carbon material to obtain a silicon-carbon negative electrode material.
[0065] After the high-temperature treatment is completed, the silicon-carbon material can be cooled in the tube furnace, then taken out, washed three times with a cleaning agent such as deionized water and ethanol, and then vacuum dried to obtain a silicon-carbon negative electrode material.
[0066] In some embodiments, the carbon material is edible ice powder, and the water-soluble silicon modified by hydroxylation is evenly dispersed in the ice powder gel, so that the ice powder-derived carbon-coated silicon composite material is obtained after high-temperature treatment, and the silicon is tightly wrapped in the carbon layer, realizing multiple ion transport channels. Moreover, the method is simple and scalable, and easy to prepare in batches.
[0067] In addition, it should be noted that the related technology uses silicon-based negative electrode materials. However, silicon-based negative electrode materials are prone to volume expansion during the cycle process. On the one hand, the breakage and pulverization of the silicon electrode causes the current collectors to lose contact, resulting in a decrease in capacity. On the other hand, the SEI film formed on the surface of the silicon electrode during volume expansion breaks during the contraction process, and the new silicon electrode surface is exposed to the electrolyte again, forming a new SEI film. The overlap of the old and new films makes the SEI film thicker and more unstable, thus causing Li + In addition, too thick SEI film will hinder Li + The transfer and diffusion of the negative electrode lead to severe polarization of the negative electrode during the cycle and the degradation of electrochemical performance. In some embodiments of the present application, nano silicon particles are used to make the silicon material into nano size, and its specific surface area will be significantly increased. When the prepared silicon-carbon negative electrode material is applied to the charging and discharging process of the lithium battery, the volume change produced by the nano silicon is relatively uniform in all directions, which can effectively disperse the stress. At the same time, the short diffusion path at the nanoscale is also conducive to the rapid embedding and extraction of lithium ions, improving the rate performance of the battery. In addition, in the present application, nano silicon particles are compounded with bio-carbon materials to form a silicon-carbon composite material. The bio-carbon material has good flexibility and mechanical properties, can buffer the volume change of silicon during the charging and discharging process, and enhance the structural stability of the electrode. And the carbon material can play the role of supporting and dispersing the silicon particles. At the same time, when it is subsequently applied to the battery, the carbon separates the silicon from the electrolyte to prevent contact between the two. The SEI film is generated on the surface of the carbon, which improves the conductivity and stability of the electrode and improves the overall performance of the battery.
[0068] The properties of the related substances prepared by the preparation method provided in this application are specifically described below through specific parameters.
[0069] See also Figure 5 , Figure 5 The X-ray diffraction (XRD) diagram of the prepared silicon-carbon negative electrode material shows that the diffraction peaks at 28.6°, 47.5°, 56.3°, 68.5° and 75.7° correspond to the (111), (220), (311)(400) and (331) crystal planes of crystalline silicon, respectively. The broad diffraction peaks at 17-28° and the weak diffraction peak near 43° indicate that the carbon derived from ice powder is a typical amorphous carbon.
[0070] See also Figure 6 , Figure 6 This is a comparison of the prepared hydroxy silicon material and pure silicon suspended in water for 24 hours (hydroxy silicon material on the left, pure silicon on the right). It can be seen from the figure that the hydroxy silicon material obtained after hydroxylation modification has good water solubility and can be dispersed in water as a suspension. In this way, during the cooling of the edible ice powder to form a hydrogel, the evenly distributed silicon particles are coated by the hydrogel, and this coating structure is maintained during the subsequent freeze-drying and high-temperature treatment. Moreover, the porous structure formed by the edible ice powder-derived carbon during the high-temperature treatment process can buffer the stress generated by the charging and discharging of lithium ions, and can also provide more lithium ion storage sites.
[0071] See also Figure 7 , Figure 7 This is the X-ray Photoelectron Spectroscopy (XPS) spectrum of the prepared silicon-carbon negative electrode material. Since the original image is a color image, in order to distinguish different lines, arrows are used to mark the lines in the figure. The arrows are in a different form from the arrows in the original image to distinguish them. Among them, Figure 7 (a) is the full XPS spectrum, in which three materials, C, O, and Si, can be clearly observed. The presence of O atoms is mainly due to the hydroxyl groups grafted on the surface of the silicon material or the residual oxygen-containing functional groups of graphene oxide during the high-temperature reduction process. Figure 7 (b) is the fitting diagram of Si 2p peak. The two fitting peaks appearing at 99.8 eV and 103.8 eV correspond to Si-O bonds and Si-Si bonds, respectively. This may be because the hydroxylation modification causes more hydroxyl groups to be grafted on the surface of Si, introducing more Si-O bonds, so its intensity is higher. Figure 7 (c) is the high-resolution XPS spectrum of C1s of the silicon-carbon composite negative electrode material. The CC peak at 284.80 eV corresponds to the C-Si peak at 284.3 eV, the CO peak at 286.3 eV and the C=O peak at 288.3 eV. It can be clearly seen that the intensity of the oxygen-containing functional groups is low, indicating that most of the oxygen-containing functional groups on the graphene sheets have been removed, which reduces the resistance of the silicon-carbon negative electrode material and increases its conductivity. Therefore, when applied to lithium-ion batteries, the resistance of the lithium ion deintercalation process is reduced, which is beneficial to its electrochemical performance.
[0072] See also Figure 8 , Figure 8This is a scanning electron microscope (SEM) image of the prepared silicon-carbon negative electrode material. From this SEM image, we can see that the silicon particles have a uniform particle size, and after being coated with carbon, the whole is flaky. The silicon nanoparticles are evenly distributed and have a porous structure. The carbon is relatively evenly coated on the surface of the silicon nanoparticles. This structure can preferentially buffer the stress generated by the insertion and removal of lithium ions during the charge and discharge process, and at the same time stabilize the SEI film on the surface of the carbon shell layer, thereby improving the cycle stability performance.
[0073] This application also provides a method for preparing a silicon-carbon negative electrode. Fig. 9 In some embodiments, the method for preparing the silicon-carbon negative electrode comprises:
[0074] Step S10, obtaining hydroxy silicon material;
[0075] Step S20, mixing the hydroxy silicon material and the carbon material to obtain a silicon-carbon gel;
[0076] Step S30, subjecting the silicon-carbon gel to high-temperature treatment to obtain a silicon-carbon negative electrode material;
[0077] Step S40, mixing the silicon-carbon negative electrode material with a conductive agent and a binder to prepare a slurry mixture;
[0078] Among them, the conductive agent can be carbon black, acetylene black, graphite, carbon fiber, carbon nanotube, graphene, etc., and the binder can be sodium alginate, styrene-butadiene latex, sodium carboxymethyl cellulose, polyvinyl alcohol, polytetrafluoroethylene, polyvinylidene fluoride, polypropylene, polyimide, etc.
[0079] In some embodiments, the conductive agent is carbon black and the binder is sodium alginate, wherein the mass percentage of sodium alginate is 3wt%, and the mass ratio of the silicon-carbon negative electrode material, the conductive agent, and the binder is 6-8:1-2:1-2, specifically 6:2:2, 7:1.5:1.5, 8:1:1, etc., which is not limited here.
[0080] During the preparation process, the concentration can be adjusted by adding water dropwise to obtain a slurry mixture with appropriate consistency.
[0081] Step S50, coating the slurry mixture on the negative electrode current collector and performing drying treatment to obtain a silicon-carbon negative electrode.
[0082] The negative electrode current collector may be made of copper foil, which may be coated on the copper foil by a coater, and then dried in a vacuum drying oven at 80°C-90°C for 8h-12h before being taken out. The electrode foil may be cut into 14mm diameter electrode sheets by a sheet cutter.
[0083] Specifically, the temperature of the vacuum drying oven can be 80°C, 82°C, 84°C, 86°C, 88°C, 90°C, etc., and the drying time can be 8h, 9h, 10h, 11h, 12h, etc., which is not specifically limited here.
[0084] Among them, steps S10-S30 are the same as those in the above-mentioned embodiment of the method for preparing the silicon-carbon negative electrode material. For relevant details, please refer to the above-mentioned embodiment and will not be repeated here.
[0085] It should be noted that, through the above method, the hydroxy silicon material in the silicon-carbon gel can be evenly dispersed, so that in the obtained silicon-carbon negative electrode material, the silicon is tightly wrapped in the carbon layer, and the internal micropores are interconnected. Therefore, the obtained silicon-carbon negative electrode not only meets the high specific capacity but also has good SEI membrane stability and multiple ion transport channels, thereby improving the electrochemical performance of the corresponding lithium battery.
[0086] The present application also provides a silicon-carbon negative electrode, which can be prepared by the preparation method of the silicon-carbon negative electrode before the present application. For relevant details, please refer to the above embodiment, which will not be repeated here.
[0087] It should be noted that in the silicon-carbon negative electrode in this embodiment, silicon is tightly wrapped in the carbon layer, and the internal micropores are interconnected. On the basis of meeting the high specific capacity, it also has good SEI film stability and has multiple ion transport channels, which can improve the electrochemical performance of the corresponding lithium battery.
[0088] See also Fig.10 , Fig.10 This is the CV curve of the silicon-carbon negative electrode. Fig.10 The cyclic voltammetry curves of the first three cycles of the electrode at a scan rate of 0.1mV / s are specifically described. Since the original image is a color image, arrows are used to distinguish different lines. During the first discharge process, the electrode shows a broad reduction peak at about 1.0V-1.2V, which represents the complex reaction process of lithium ions forming the SEI film and is related to the defective lithium storage at the edge of the carbon. This peak no longer appears in subsequent cycles, and the subsequent cycles are highly overlapped, which is consistent with the irreversibility of the reaction and the stability of the SEI film. In the subsequent cathode scan process, the weak peak at about 0.21V corresponds to the lithium-silicon alloy, which gradually increases with the increase in the number of cycles. In the anodic scan process, the peaks at 0.35V and 0.53V correspond to the process of Li and Si dealloying, and the intensity gradually increases in three cycles, that is, further dealloying occurs with the increase in the number of cycles.
[0089] The present application also provides a lithium battery, which includes a positive electrode, a negative electrode, a diaphragm, an electrolyte and a shell, wherein the diaphragm is located between the positive electrode and the negative electrode, and the shell is located outside the positive electrode, the negative electrode, the diaphragm and the electrolyte.
[0090] The negative electrode is a silicon-carbon negative electrode prepared according to the method for preparing a silicon-carbon negative electrode as described above. For details, please refer to the above embodiment and will not be described again here.
[0091] It should be noted that in the present embodiment, in the negative electrode of the lithium battery, silicon is tightly wrapped in the carbon layer, and the internal micropores are interconnected, which not only meets the high specific capacity but also has good SEI membrane stability and has multiple ion transport channels, which can improve the electrochemical performance of the lithium battery.
[0092] The technical solution of the present invention is further illustrated by specific examples below. The examples are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0093] Example 1
[0094] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0095] (1) Silicon nanoparticles were stirred in a mixture of H2SO4 and H2O2 (H2SO4:H2O2=7:3 v / v) at 85°C for 30 min, washed with deionized water and ethanol for three times, and then vacuum dried to obtain hydroxy silicon material Si-OH.
[0096] (2) Take an appropriate amount of Si-OH and dissolve it in deionized water, heat it to 98°C to obtain a hydroxy-silicon mixed solution, then add ice powder to the hydroxy-silicon mixed solution, wherein the mass ratio of silicon to ice powder is 1:2, stir evenly and cool to room temperature to obtain a brown-yellow silicon-carbon gel, and freeze-dry the silicon-carbon gel; then put the freeze-dried silicon-carbon gel into a tubular furnace, heat the tubular furnace at 5°C per minute to 700°C and keep it warm for 2 hours, take it out after natural cooling, wash it with deionized water and ethanol for 3 times, and then obtain the silicon-carbon negative electrode material after vacuum drying.
[0097] (3) The silicon-carbon negative electrode material obtained in (2) was mixed with conductive carbon black and a binder (sodium alginate, 3 wt%) in a ratio of 8:1:1 to obtain a slurry mixture, and the concentration of the slurry mixture was adjusted by dripping water to obtain a slurry mixture with moderate consistency; then the slurry mixture was coated on a copper foil by a coater, and dried in a vacuum drying oven at 80° C. for 12 h before being taken out. The electrode sheets with a diameter of 14 mm were cut by a sheet cutter.
[0098] Example 2
[0099] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0100] (1) Silicon nanoparticles were stirred in a mixture of H2SO4 and H2O2 (H2SO4:H2O2=8:2 v / v) at 85°C for 30 min, washed with deionized water and ethanol three times, and then vacuum dried to obtain hydroxy silicon material Si-OH.
[0101] (2) Take an appropriate amount of Si-OH and dissolve it in deionized water, heat it to 98°C to obtain a hydroxy-silicon mixed solution, then add ice powder to the hydroxy-silicon mixed solution, wherein the mass ratio of silicon to ice powder is 1:1, stir evenly and cool to room temperature to obtain a brown-yellow silicon-carbon gel, and freeze-dry the silicon-carbon gel; then put the freeze-dried silicon-carbon gel into a tubular furnace, heat the tubular furnace to 800°C at 5°C per minute and keep it warm for 1 hour, take it out after natural cooling, wash it with deionized water and ethanol for 3 times, and then obtain the silicon-carbon negative electrode material after vacuum drying.
[0102] (3) The silicon-carbon negative electrode material obtained in (2) was mixed with conductive carbon black and a binder (sodium alginate, 3 wt%) in a mass ratio of 8:1:1 to obtain a slurry mixture, and the concentration of the slurry mixture was adjusted by dripping water to obtain a slurry mixture with moderate consistency; then the slurry mixture was coated on a copper foil by a coater, and dried in a vacuum drying oven at 90° C. for 8 h before being taken out. The electrode sheets with a diameter of 14 mm were cut by a sheet cutter.
[0103] Example 3
[0104] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0105] (1) Silicon nanoparticles were stirred in a mixture of H2SO4 and H2O2 (H2SO4:H2O2=7:3 v / v) at 85°C for 10 min, washed with deionized water and ethanol three times, and then vacuum dried to obtain hydroxy silicon material Si-OH.
[0106] (2) Take an appropriate amount of Si-OH and dissolve it in deionized water, heat it to 98°C to obtain a hydroxy-silicon mixed solution, then add ice powder to the hydroxy-silicon mixed solution, wherein the mass ratio of silicon to ice powder is 1:3, stir evenly and cool to room temperature to obtain a brown-yellow silicon-carbon gel, and freeze-dry the silicon-carbon gel; then put the freeze-dried silicon-carbon gel into a tubular furnace, heat the tubular furnace to 500°C at 3°C per minute, keep it warm for 1 hour, and then continue to heat it to 800°C and keep it warm for 2 hours, take it out after natural cooling, wash it with deionized water and ethanol for 3 times, and then obtain the silicon-carbon negative electrode material after vacuum drying.
[0107] (3) The silicon-carbon negative electrode material obtained in (2) was mixed with conductive carbon black and a binder (sodium alginate, 3 wt%) in a mass ratio of 7:1.5:1.5 to obtain a slurry mixture, and the concentration of the slurry mixture was adjusted by dripping water to obtain a slurry mixture with moderate consistency; then the slurry mixture was coated on a copper foil by a coater, and dried in a vacuum drying oven at 80° C. for 12 h before being taken out. The electrode sheets with a diameter of 14 mm were cut by a sheet cutter.
[0108] Example 4
[0109] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0110] (1) Silicon nanoparticles were stirred in a mixture of H2SO4 and H2O2 (H2SO4:H2O2=9:1 v / v) at 85°C for 30 min, washed with deionized water and ethanol three times, and then vacuum dried to obtain hydroxy silicon material Si-OH.
[0111] (2) Take an appropriate amount of Si-OH and dissolve it in deionized water, heat it to 98°C to obtain a hydroxy-silicon mixed solution, then add ice powder to the hydroxy-silicon mixed solution, wherein the mass ratio of silicon to ice powder is 1:2, stir evenly and cool to room temperature to obtain a brown-yellow silicon-carbon gel, and freeze-dry the silicon-carbon gel; then put the freeze-dried silicon-carbon gel into a tubular furnace, heat the tubular furnace to 800°C at 3°C per minute, keep it warm for 2 hours, take it out after natural cooling, wash it with deionized water and ethanol three times, and then obtain the silicon-carbon negative electrode material after vacuum drying.
[0112] (3) The silicon-carbon negative electrode material obtained in (2) was mixed with conductive carbon black and a binder (sodium alginate, 3 wt%) in a mass ratio of 6:2:2 to obtain a slurry mixture, and the concentration of the slurry mixture was adjusted by dripping water to obtain a slurry mixture with moderate consistency; then the slurry mixture was coated on a copper foil by a coater, and dried in a vacuum drying oven at 80° C. for 12 h before being taken out. The electrode sheets with a diameter of 14 mm were cut by a sheet cutter.
[0113] Example 5
[0114] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0115] (1) Silicon nanoparticles were stirred in a mixture of H2SO4 and H2O2 (H2SO4:H2O2=7:3 v / v) at 85°C for 20 min, washed with deionized water and ethanol for three times, and then vacuum dried to obtain hydroxy silicon material Si-OH.
[0116] (2) Take an appropriate amount of Si-OH and dissolve it in deionized water, heat it to 98°C to obtain a hydroxy-silicon mixed solution, then add ice powder to the hydroxy-silicon mixed solution, wherein the mass ratio of silicon to ice powder is 1:3, stir evenly and cool to room temperature to obtain a brown-yellow silicon-carbon gel, and freeze-dry the silicon-carbon gel; then put the freeze-dried silicon-carbon gel into a tubular furnace, heat the tubular furnace to 500°C at 5°C per minute, keep it warm for 1 hour, continue to heat it to 700°C and keep it warm for 3 hours, take it out after natural cooling, wash it with deionized water and ethanol for 3 times, and then obtain the silicon-carbon negative electrode material after vacuum drying.
[0117] (3) The silicon-carbon negative electrode material obtained in (2) was mixed with conductive carbon black and a binder (sodium alginate, 3 wt%) in a mass ratio of 8:1:1 to obtain a slurry mixture, and the concentration of the slurry mixture was adjusted by dripping water to obtain a slurry mixture with moderate consistency; then the slurry mixture was coated on a copper foil by a coater, and dried in a vacuum drying oven at 80° C. for 10 h before being taken out. The electrode sheets with a diameter of 14 mm were cut by a sheet cutter.
[0118] Comparative Example 1
[0119] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0120] (1) The silicon nanoparticles were washed with deionized water and ethanol for three times and then vacuum dried to obtain treated nano-silicon.
[0121] (2) Take an appropriate amount of nano-silicon and dissolve it in deionized water, heat it to 98°C, add ice powder, wherein the mass ratio of silicon to ice powder is 1:2, stir evenly and cool to room temperature to obtain brown-yellow silicon-carbon gel, and freeze-dry the silicon-carbon gel; then put the freeze-dried silicon-carbon gel into a tubular furnace, heat the tubular furnace to 700°C at 5°C per minute and keep it warm for 2 hours, take it out after natural cooling, wash it with deionized water and ethanol for 3 times, and then obtain the silicon-carbon negative electrode material after vacuum drying.
[0122] (3) The silicon-carbon negative electrode material obtained in (2) was mixed with conductive carbon black and a binder (sodium alginate, 3 wt%) in a mass ratio of 8:1:1 to obtain a slurry mixture, and the concentration of the slurry mixture was adjusted by dripping water to obtain a slurry mixture with moderate consistency; then the slurry mixture was coated on a copper foil by a coater, and dried in a vacuum drying oven at 80° C. for 12 h before being taken out. The electrode sheets with a diameter of 14 mm were cut by a sheet cutter.
[0123] Comparative Example 2
[0124] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0125] (1) Silicon nanoparticles were stirred in a mixture of H2SO4 and H2O2 (H2SO4:H2O2=7:3 v / v) at 85°C for 30 min, washed with deionized water and ethanol for three times, and then vacuum dried to obtain hydroxy silicon material Si-OH.
[0126] (2) Take an appropriate amount of Si-OH and dissolve it in deionized water, heat it to 98°C to obtain a hydroxy-silicon mixed solution, then add petroleum coke to the hydroxy-silicon mixed solution, wherein the mass ratio of silicon to petroleum coke is 1:2, stir evenly and cool to room temperature to obtain a brown-yellow silicon-carbon gel, and freeze-dry the silicon-carbon gel; then put the freeze-dried silicon-carbon gel into a tubular furnace, heat the tubular furnace to 700°C at 5°C per minute, keep it warm for 2 hours, take it out after natural cooling, wash it with deionized water and ethanol three times, and then obtain the silicon-carbon negative electrode material after vacuum drying.
[0127] (3) The silicon-carbon negative electrode material obtained in (2) was mixed with conductive carbon black and a binder (sodium alginate, 3 wt%) in a mass ratio of 8:1:1 to obtain a slurry mixture, and the concentration of the slurry mixture was adjusted by dripping water to obtain a slurry mixture with moderate consistency; then the slurry mixture was coated on a copper foil by a coater, and dried in a vacuum drying oven at 80° C. for 12 h before being taken out. The electrode sheets with a diameter of 14 mm were cut by a sheet cutter.
[0128] The electrode sheets obtained in Examples 1-5 and Comparative Examples 1-2 were used as negative electrodes, circular metal lithium sheets were used as counter electrodes, LiPF6 solution was used as electrolyte, Celgar2500 was used as separator, and CR2032 button cells were used for assembly in a glove box filled with Ar2 (water content <0.1ppm, oxygen content <0.1ppm). After the assembly was completed, the battery was left to stand at room temperature of 25°C for 12 hours, and the cycle performance of the battery was determined by repeated constant current charge and discharge at a constant current density, and the charge and discharge cut-off voltage was 3.0V-0.01V.
[0129] Results of charge and discharge cycle tests of silicon-carbon negative electrode materials of Examples 1-5 and Comparative Examples 1-2
[0130]
[0131] Referring to the results of the above-mentioned Examples 1-5 and Comparative Examples 1-2, it can be seen that the present application modifies the nano-silicon particles, mixes the modified nano-silicon soluble in water with the biomass carbon material ice powder to obtain a hydrogel, and further freezes and performs high-temperature treatment to obtain a silicon-carbon negative electrode material, which can significantly improve the cycle charge and discharge performance of the battery.
[0132] The above are only implementation methods of the present application, and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. A method for preparing a silicon-carbon negative electrode material, characterized in that: include: Obtaining hydroxy silicon material; Mixing the hydroxy silicon material with the carbon material to obtain a silicon-carbon gel; The silicon-carbon gel is subjected to high-temperature treatment to obtain the silicon-carbon negative electrode material.
2. The method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: The carbon material comprises konjac glucomannan.
3. The method for preparing the silicon-carbon negative electrode material according to claim 2, characterized in that: The carbon material is a biomass carbon material.
4. The method for preparing the silicon-carbon negative electrode material according to claim 3, characterized in that: The biomass carbon material includes at least one of ice powder and konjac products.
5. The method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: The obtaining of hydroxy silicon material comprises: Adding nano silicon particles to the sulfuric acid and hydrogen peroxide mixture to perform hydroxylation on the nano silicon particles to obtain a hydroxy silicon mixture; The hydroxy silicon mixture is cleaned to obtain the hydroxy silicon material.
6. The method for preparing the silicon-carbon negative electrode material according to claim 5, characterized in that: The step of adding nano silicon particles to the sulfuric acid and hydrogen peroxide mixture to perform hydroxylation on the nano silicon particles to obtain a hydroxy silicon mixture comprises: Adding the nano-silicon particles to the sulfuric acid and hydrogen peroxide mixture at 80° C.-85° C. and with a volume ratio of sulfuric acid to hydrogen peroxide of 7-9:1-3, and stirring for 10 min-30 min to obtain the hydroxy silicon mixture; The step of washing the hydroxy silicon mixture to obtain the hydroxy silicon material comprises: The hydroxy silicon mixture is washed with deionized water and ethanol, and then dried to obtain the hydroxy silicon material.
7. The method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: The step of mixing the hydroxy silicon material with the carbon material to obtain the silicon-carbon gel comprises: Dissolving the hydroxy silicon material in deionized water and heating it to 95°C-98°C to obtain a hydroxy silicon mixed solution; The carbon material is added to the hydroxy-silicon mixed solution, stirred and cooled to room temperature to obtain the silicon-carbon gel, wherein the mass ratio of silicon in the hydroxy-silicon material to the carbon material is 1:1-3.
8. The method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: The step of subjecting the silicon-carbon gel to high temperature treatment to obtain the silicon-carbon negative electrode material comprises: The silicon-carbon gel is subjected to high-temperature treatment to obtain a silicon-carbon material, wherein during the high-temperature treatment, the temperature is increased to 500° C.-800° C. at 3° C.-5° C. per minute and kept at this temperature for 1 h-3 h; The silicon-carbon material is cooled, cleaned and dried to obtain the silicon-carbon negative electrode material.
9. The method for preparing the silicon-carbon negative electrode material according to claim 8, characterized in that: Also includes: freeze-drying the silicon-carbon gel to obtain freeze-dried silicon-carbon gel; The step of subjecting the silicon-carbon gel to high temperature treatment to obtain the silicon-carbon material comprises: The freeze-dried silicon-carbon gel is subjected to high-temperature treatment to obtain the silicon-carbon material.
10. A method for preparing a silicon-carbon negative electrode, characterized in that: include: Obtaining a silicon-carbon negative electrode material, wherein the silicon-carbon negative electrode material is prepared by the method for preparing a silicon-carbon negative electrode material according to any one of claims 1 to 9; The silicon-carbon negative electrode material is mixed with a conductive agent and a binder to prepare a slurry mixture; The slurry mixture is coated on a negative electrode current collector and dried to obtain the silicon-carbon negative electrode.
11. A silicon-carbon negative electrode, characterized in that: The silicon-carbon negative electrode is prepared by the method for preparing the silicon-carbon negative electrode according to claim 10.
12. A lithium battery, characterized in that: It includes a positive electrode, a negative electrode, a separator, an electrolyte and a shell, wherein the separator is located between the positive electrode and the negative electrode, and the shell is located outside the positive electrode, the negative electrode, the separator and the electrolyte; Wherein, the negative electrode is a silicon-carbon negative electrode prepared by the method for preparing a silicon-carbon negative electrode according to claim 10.
Citation Information
Patent Citations
Application of konjac glucomannan to bonding agent
CN108232109A
Silicon-carbon negative electrode slurry and preparation method and application thereof
CN109950540A
High-specific-capacity silicon-carbon negative electrode material as well as preparation method and application thereof
CN116477600A
